SCIENCE, TECHNOLOGY, AND GLOBALIZATION: A RE-APPRAISAL IN THE PHILOSOPHY OF SCIENCE AND TECHNOLOGY - Obi-Okogbuo, Jerry (European Scientific Journal, ESJ, 2015)
Every age has got its age-mark; the outstanding feature characteristic that defines that age. Our age, the 21st century, like the one before it, is defined by globalization. Historical philosophers or dialecticians, those who perceive an underlying logic in history, believe that no phase of life comes to a close until it has exhausted all its possibilities. It is obvious that globalization has not exhausted its possibilities. Globalization is still in progress. It is still the defining mark of our age. There is therefore the need to re-appraise it to raise fundamental philosophical questions about it; such questions as relate to the phenomenology of globalization; the philosophical foundations of globalization; the symbiotic and synergistic relationship between science and technology as the force driving globalization; and the cost-benefit analysis of globalization. It is only when these questions are philosophically re-appraised that we would hope to effectively function and contribute in our globalized world, a competitive, participators and interactive world. Since the Kernel of this paper is about re-appraising the symbiotic and synergistic relationship between science and technology as the motor driving globalization, our approach is that of the philosophy of science and technology.